The Impact of Competency, Workload, and Work Environment to Work Stress and The Employee Performance of Bank BJB S. Parman - Indyra Dwi Cahyaningtyas; Allicia Deana Santosa (Forum Inovasi Bisnis dan Manajemen, 2021)
Demands from management so that employees increase competency by increasing workloads coupled with a non-conducive work environment often cause employees to experience stress and decrease performance. The purpose of this research is to know the influence of the competency, workload, the work environment on work stress, and the employee performance of Bank BJB Branch of S. Parman. The sampling total used in this research is 100 respondents. The research method used is the verification method (quantitative) with analytical tools in the form of validity, reliability, coefficient of determination, and hypothesis testing (t-test and F test). The measurement of the data is performed by Likert scale questionnaire 5-points. Based on the t-test results shows the calculated t-value is greater than the t-table (1.996), except for the work environment variable. The results showed that the competency and the workload of a positive and significant effect on the stress of work and performance, while the influential work environment variable is positive and significant but not to work stress and employee performance.